Powering Inaccessible IoT Devices Through a WPT-enabled Sustainable UAV Network - Mekikis, Prodromos Vasileios; Bouzinis, Pavlos; Mitsiou, Nikos; Tegos, Sotiris; Papanikolaou, Vasilis K.; Tyrovolas, Dimitrios; Diamantoulakis, Panagiotis; Karagiannidis, George K. (IEEE INFOCOM 2023 - Conference on Computer Communications Workshops, INFOCOM WKSHPS 2023, 2023)
Powering Internet of Things (IoT) devices in hard to reach or hazardous locations could be prohibitive in terms of cost and safety. In this work, we demonstrate a thorough solution that tackles this problem using a network of unmanned aerial vehicles (UAVs) with wireless power transfer (WPT) capabilities. Given the large-scale IoT deployments of the future and the energy needs of the UAVs, we consider an infrastructure of charging stations for the UAVs that allow an uninterrupted and flexible UAV deployment based on the current energy needs of the IoT devices. Then, we exhibit an orchestrator that communicates with the entire infrastructure and handles the UAV traffic and energy decisions, as well as the digital representation and interaction of the network with the user.
Created from Fastlane, Scopus look-up
Keywords: energy coverage; orchestrator; Unmanned aerial vehicles; user interface; Wireless power transfer